Analysis Of The Influence Of Customer Satisfaction On Sharia Banking Peroformance In Bogor City - Arfiana Burhan, R Dina; Najib, Muhammad; Endri, Endri (CV. Inara, 2021)
The development of Islamic banking is very rapid, causing competition between Islamic and conventional banking. Improving the quality of services and products makes the main point in providing customer satisfaction. This study aims to analyze the influence of service quality, product quality, and price with customer satisfaction at Islamic commercial banks in the city of Bogor. This study uses SEM (Structural Equation Modeling) to determine the level of influence of the relationship between customer satisfaction with service quality, product quality and price. This study used a sample of 100 respondents with qualifications of 81 men and 19 women and used a descriptive approach. The results of this study are the level of customer satisfaction with prices reaching 2.49, besides that the level of customer satisfaction with products is 2.91, and the level of customer satisfaction with service quality is 2.84. These results prove that customer satisfaction is strongly influenced by the price, products, and quality of services provided by Islamic banking.